(untitled) (Research, Society and Development, 2020)
Medical training needs to find a balance between the contents that will be listed in the curriculum, so that they really benefit the training of the doctor. We realized that dermatological complaints are very frequent complaints among patients, not only in Brazil but in other countries. Even so, so far, little importance is given to what approach will be given to skin disorders during medical graduation, with only 1% of the time of graduation being allocated to teaching dermatology. This article aims to bring a review on the teaching of dermatology in Medical Graduation, showing how the training of doctors in this specialty is being. The methodological path consisted of searching for articles from five bibliographic databases - PubMed, Web of Science, EMBASE, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and LILACS from 1971 to 2018, in Portuguese, English, Spanish and German, with the keywords medical graduation, medical curriculum, basic curriculum in dermatology, relevant content in dermatology, combined with the associations and outcomes of interest. The selected articles were used to support the writing on dermatology content relevant to medical training. In the end it was demonstrated how some countries including the USA, Australia and Switzerland organize the dermatology contents within their medical curricula and thus provide the training of professionals better prepared to work in dermatology.